Bureaucracy in a Democratic State A Governance Perspective - K E N N E T H J . M E I E R, L A U R E N C E J . O â€™ T O O L E J R . (The Johns Hopkins University Press, 2006)
Can the imperatives of an administrative system be reconciled with the norms of democratic governance? Or is bureaucracy, with its expertise, insulation, and byzantine procedures, the enemy of popular control? These questions have been raised wherever administrative institutions have been a key element in a broader pattern of purportedly democratic rule. Deep suspicions have typically been aroused in situations in which anonymous bureaucrats and their managers make decisions that affect the outputs and outcomes of public policy. Bureaucrats themselves, on the other hand, have been known to treat political overseers with some suspicion, if not outright disdain and evasion. These tensions have not dissipated with the rise of more complex patterns of â€œgovernanceâ€ that encompass multiple organizations and stakeholders in networks to co-produce policy resultsâ€”a set of developments receiving particular attention recently in Western Europe and North America. Indeed, the challenges posed by such broadened notions of â€œbureaucracy,â€ loosely speaking, for democratic governance are even greater. In this book, we address these central questions by examining the results of bureaucratic and political interactions in some governance settings, to test for several of the most frequently mentioned, or feared, patterns of infl uence and to see whether bureaucratic systems weaken or strengthen the connections between public preferences and policy results. We make use of two sets of conceptual lenses: the mainstream perspective of political science on the bureaucracy-democracy nexus and the standard treatment of the subject in the research literature on public administration. Political science typically sees the democratic impulse as shaping bureaucracy, if at all, from above. The literature in this fi eld assumes the necessity for â€œpolitical controlâ€ of administrative systems by political overseers, and it tests for the health of democratic systems by seeking evidence that those at the top direct those at the bottom. Although relevant for considering the question of bureaucracy and democracy,we argue that this approach suffers from many serious limitations and does not effectively get at the nub of the issue.